“Eu não trabalho de outra forma, eu penso Enem”: a proposta de redação do Enem e suas implicações no trabalho com produção de texto em sala de aula - Silva , Bruna Costa (2017)
Given the current Portuguese Language Teaching perspective, especially from the use of the Brazilian National Examination of Secondary School (ENEM) as the main form of College Education access, we consider the need to understand the writing activity within the new configuration assumed for the Portuguese Language (PL) classes, seeking to observe the relations that are established among the main agents involved in this process. Therefore, we tried to understand how the prescriptions presented in the official documents that regulate the elaboration of ENEM have guided the Portuguese Language teacher work in the classes of textual production that are concerned, as well as the reflexes of the accomplishment of this work in the Students' written activity. In order to reach the proposed objective, we chose ENEM /teacher /student triad, and took as the object of analysis, the official documents elaborated by INEP/MEC, interviews with the teachers, and the observation of textual production classes, produced by students. Thus, for the development of this exploratory research, with a qualitative-interpretative and documentary basis, we had the collaboration of two PL teachers, who work in state high schools in the city of João Pessoa - Paraíba, as well as 62 students of both teachers. As a base, to support the analysis, we took the theoretical-methodological framework of Socio-Discursive Interactionism (SDI), in interface with the assumptions of Ergonomics, based on what Bronckart (1999, 2006, 2008), Bulea (2010), Machado (2009), Amigues (2004), Tardif and Lessard (2013), among other authors who seek to understand the relationships that constitute human interaction. Zabala and Arnou (2010) ground our discussion with regard to the competence concept and Bronckart and Machado (2004), to capacity. The discussion undertaken throughout the study points to a new look at the text production class, coming from the school writing genre reconfiguration, to fit the argumentative text model. The methodology adopted by the teachers is driven by the need for teaching skills and, the written production of the students carries the most objective traits related to the planning text, which is associated with the skills that determine these characteristics and which have been worked in a more exhaustive way in classes.